DAMPAK KEBIJAKAN PPKM BAGI PERKEMBANGAN PEREKONOMIAN UMKM DI KELURAHAN PUCANG (Jurnal Bisnis Indonesia, 2022)
The PPKM policy implemented by each Regional Government results in problems that arise in the wheels of the economy that exist in the community. The problems that arise do not exclude SMEs in Pucang Village because during the Covid-19 Pandemic they have experienced a decline in income, this interests us to examine how the impact of PPKM policies for SMEs in Pucang Village which experienced a decline in the economy previously caused by the Covid Pandemic -19. This study aims to determine how much impact the PPKM policy has on the economic development of MSME’s in Kelurahan Pucang Kabupaten Sidoarjo. The research method that we use in this study is a descriptive qualitative research method with data collection techniques using interviews and observations. The results we obtained in this study are that one of the impacts of this policy is the decline in the income of MSMEs around the Pucang village. The difficulty of turning the wheels of the local economy is because many residents depend on the income of these businesses. To be able to increase income, MSME actors market their products through online marketing such as marketplaces.  DOI : https://doi.org/10.33005/jbi.v13i1.3076